Kesiapan Supplier Komponen Otomotif di Masa Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) - Basuki Basuki (JURNAL CITRA WIDYA EDUKASI, 2021)
The Covid-19 pandemic has spread to all corners of the world including Indonesia, so the Indonesian government is trying to prevent and reduce its spread by restricting community activities known as Large-Scale Social Restrictions (PSBB) and Implementation of Community Activity Restrictions (PPKM). These restrictions will directly affect the economic cycle and industrial activities, so that the problem faced in the industrial world is the disruption of the supply of goods due to the company's limited operating hours. The same thing is also faced by automotive companies during this PPKM period, where being able to produce depends on the readiness of their suppliers. The purpose of this study was to determine the readiness of automotive companies (suppliers) in this PPKM period. The research was conducted by sending a questionnaire to 138 automotive supply companies regarding the readiness to supply components during the PPKM period. The results of this study indicate that most of the suppliers (97.1%) stated their ability to supply components and a small part (1.45%) said they were unable and some 1.45% did not give an answer. Most of the companies that provide delivery capability (93.48%) state that they are able to fulfill 80.01% to 100% of the production forecast. This means, not all suppliers can meet the producer's demand 100%, so producers must reconsider their production plans according to the ability and conditions of their suppliers.